Measuring E-Satisfaction Performance Based on Customer Smart Shopping Feeling and Confident - Mahmud Mahmud; Febrianur I F S Putra (Jurnal Manajemen Industri dan Logistik, 2022)
Recently, many people have been switching from conventional shopping to digital shopping. Even so, people feel that online shopping is less secure. Finally, many consumers search for information online before shopping at online stores. This study investigates how webrooming affects consumers' experience and determines the effect of webrooming on consumer confidence, smart shopping feeling, and e-satisfaction in the digital fashion industry. The population in this study were all the digital fashion industry consumers who experience webrooming in the shopping process. The total sample used in this study was 384 people using purposive sampling. The result obtained from this study finds that webrooming has a significant and positive effect on confidence and smart shopping feeling. Both factors, confidence and smart shopping feeling subsequently significant and positively affect e-satisfaction.